2010
DOI: 10.1088/0957-4484/21/14/145306
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Ga+irradiation on the transport properties of mesoscopic conducting thin films

Abstract: Abstract. We studied the influence of 30 keV Ga + -ions -commonly used in focused ion beam (FIB) devices -on the transport properties of thin crystalline graphite flake, La 0.7 Ca 0.3 MnO 3 and Co thin films. The changes of the electrical resistance were measured in-situ during irradiation and also the temperature and magnetic field dependence before and after irradiation. Our results show that the transport properties of these materials strongly change at Ga + fluences much below those used for patterning and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…the sample-dependent distance between interfaces along the c−axis of the graphite structure, it is appealing to argue that metalliclike interfaces are the origin for the SdH oscillations. In a different experiment the SdH oscillations were enhanced notably by ion irradiation of a 15 nm thick graphite flake, which hardly showed SdH oscillations before irradiation [28,34]. These early experiments clearly suggest that the SdH oscillations are not intrinsic of the ideal graphite structure but they are related to defective regions in the graphite sample.…”
Section: Shubnikov-de Haas Oscillationsmentioning
confidence: 90%
“…the sample-dependent distance between interfaces along the c−axis of the graphite structure, it is appealing to argue that metalliclike interfaces are the origin for the SdH oscillations. In a different experiment the SdH oscillations were enhanced notably by ion irradiation of a 15 nm thick graphite flake, which hardly showed SdH oscillations before irradiation [28,34]. These early experiments clearly suggest that the SdH oscillations are not intrinsic of the ideal graphite structure but they are related to defective regions in the graphite sample.…”
Section: Shubnikov-de Haas Oscillationsmentioning
confidence: 90%
“…Energy dispersive x-ray spectroscopy (EDAX) measurements were made to check for the sample impurities revealing a concentration of ∼2% of Ga in that surface near region. Independently done studies of the change in transport properties of thin graphite flakes after Ga + irradiation showed that the metallic-like behavior is destroyed and a large increase in electrical resistance is observed already at much lower Ga + fluences [30].…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The four-contact method used to measure the voltage response allows us to obtain the contribution of the inner part of the lamellae, i.e. of the nonmodified region because its resistance with its interfaces is much smaller than the irradiated layer [30].…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…[31], in comparison with the rather weak 6 amplitudes, if observed at all, found nowadays in better quality samples or thin enough graphite samples. A clear demonstration that these SdH oscillations are actually non-intrinsic to ideal graphite is given by their appearance in thin graphite samples upon introducing defects by irradiation as shown in [15,32].…”
Section: Temperature Dependence Of the Carrier Densitymentioning
confidence: 99%